Effects of per oral cypermethrin exposure on Bcl-2 expression in granulose cells and antral follicle count of Rattus norvegicus ovaries - Indrayanti Indrayanti; Bambang Rahardjo; Hidayat Sujuti (Majalah Obstetri dan Ginekologi, 2018)
Objectives: To determine the effect of oral cypermethrin exposure on the decrease of Bcl-2 expression in granulosa cells and antral follicle count in Rattus norvegicus ovary.Materials and Methods: This was a true experimental study using post-test control group design. This study used 24 Rattus norvegicus which were divided into 4 groups, the control group, treatment group (P1) exposed to cypermethrin 10 mg/kg BW, treatment group (P2) exposed to cypermethrin 15 mg/kg BW and treatment group (P3) exposed to cypermethrin 20 mg/kg BW. The treatment groups were exposed to cypermethrin for 28 days. A surgery was conducted in proestrus phase and ovarian organs were taken. Bcl-2 expression examination was performed by using immunohistochemical method and the antral follicle count was assessed with the Hematoxillin Eosin (HE)Results: This study showed the decrease of Bcl-2 expression in cypermethrin-exposed group compared to control group. There was a decrease in antral follicles count in cypermethrin-exposed group compared to control group.Conclusion: Cypermethrin can decrease Bcl-2 expression and antral follicles count in Rattus norvegicus ovaries.